Behaviour of retrofitted steel structures using cost effective retrofitting techniques. (April 2017) - Mirza, Olivia; Shill, Sukanta Kumer; Mashiri, Fidelis; Schroot, Daniel
Abstract: Steel structures today are edging towards the end of their design life. Recently, the frequency and magnitude of loadings are becoming significantly greater in comparison to the initial design loads at the time of construction. Deterioration from prolonged exposure to environmental conditions including weathering and climate change, as well as the effects of human error, also influence the design life of these older steel structures. The research focuses on developing a comparison between the fatigue performance of 120 years old and new equivalent steel structures. The fatigue resistance of both the old riveted and new welded steel structures is evaluated by investigating and analysing the stresses at critical locations within the structures. Retrofitting techniques are applied to both the old and new structures and analyzed in terms of their capacity to increase resistance to fatigue failure and extend the design life of steel structures. The research is conducted by performing both experimental study and finite element analysis. The experimental research analyses the performance of an old riveted structure, as well as a new equivalent prefabricated hot rolled section, to determine areas which are highly susceptible to fatigue failure. The numerical analysis using the finite element package ABAQUS is conducted to model both the old and new girder. Retrofitting proposals are introduced into the FE model both with and without the fatigue induced cracking to investigate improvements in the fatigue performance of the old and new girders, as well as techniques of repairing existing damage. The retrofitting techniques are cost effective and practical in engineering today to improve the performance and loading capacities to enhance the design life of steel structures. The retrofitting techniques are innovative, cost effective and practical in engineering today to improve the performance and loading capacities to enhance the design life of steel structures. An overall conclusion determines the extent of increasing design life, enhancing profitable engineering and focus on sustainability, in comparative terms of either retrofitting an old structure or replacing it with a new steel structure.